ANDREJ BELYJ AND ISAIAH - Magnus Ljunggren (Studia Litterarum)
The theme of doom and resurrection is a constant in Andrej Belyj’s works. Catastrophism on the personal, national, overarching cultural and cosmic planes are always present. To a significant degree, of course, he draws upon Revelation, but he has a recurrent need of Isaiah’s Apocalypse and its mighty prophecy about the “city of confusion” that is condemned for its sinfulness and destroyed by the vengeful God to eventually arise in a new form. It is no coincidence that in his great novels, Belyj condemns Petersburg and Moscow as breeding grounds of disease. He regards urban civilization as hostile to humans and contrary to nature. His collected works are an echo chamber abounding in quotations and allusions. Especially often he quotes himself, returning to borrowed key phrases. An especially important passage about the sinful city from the Isaiah Apocalypse — “Fear, and the pit, and the snare, are upon thee, O inhabitant of the earth” — runs throughout Belyj’s oeuvre (since his letters should also be regarded as one of his artistic genres).